Inventarisasi Dan Analisis Jenis Anggrek (Orchidaceae) Di Kampung Nambo, Desa Batukarut, Kecamatan Arjasari, Kabupaten Bandung - Risdiana, Syahira Fahreza; Azharia, Syifa Azkia; Supriyatna, Ateng (Universitas Gajah Putih, 2023)
Orchid is a plant from the Orchidaceae family which is known for the beauty and beauty of its flowers. In Indonesia, there are various species of orchids spread across large islands such as Java and Sumatra. Therefore, orchids have a lot of richness with morphological differences in them. Because of its beauty, orchids are often used as ornamental plants to beautify the yard. Observations were made in the yard of the house in the Nambo Village area, Batukarut Village, Arjasari District, Bandung Regency to classify ornamental orchid plants and differentiate them based on their morphological characteristics. The results obtained were found to be 5 species of orchids from different genera where there were morphological differences between one another. The species is Vanda sp. (Vanda Orchid), Cymbidium Golden Boy. (Boat Orchid), Phalaenopsis amabilis (Moon Orchid), Dendrobium caesar and Arachnis flos-aeris (Scorpion Orchid).